1983
DOI: 10.1159/000469613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Castration and Testosterone Substitution on the Urinary Output of Gamma-Glutamyl Transpeptidase and of N-Acetyl-Beta-D-GIucosaminidase of Male Rats with Renovascular Hypertension

Abstract: The effect of castration of male rats with experimental renal hypertension (‘two kidney Goldblatt hypertension’) was studied on the height of the hypertension and on the urinary output of γ-glutamyl transpeptidase (γGT) and of N-acetyl-beta-D-glucosaminidase (NAG). Castration was carried out immediately after clamping one renal artery. Some of the castrates received testosterone substitution from the 3rd postoperative week onwards. Uncastrated hypertensive males served as controls. The experiments were carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…It seems that mais, but obviously renovascular hyperten-testosterone is implicated in the time-depension could interfere with enzymuria as re-dent increase of urinary AAP and y-GT obported for other renal enzymes such as kalli-served under normal growth development in krein [11,12]. In spite of these differences of male rats, protocol, our results are consistent with the study of Malyuz and Ehrens [8] regarding the effect of castration and testosterone on uri nary excretion of y-GT.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It seems that mais, but obviously renovascular hyperten-testosterone is implicated in the time-depension could interfere with enzymuria as re-dent increase of urinary AAP and y-GT obported for other renal enzymes such as kalli-served under normal growth development in krein [11,12]. In spite of these differences of male rats, protocol, our results are consistent with the study of Malyuz and Ehrens [8] regarding the effect of castration and testosterone on uri nary excretion of y-GT.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge only one study [8] has investigated the influence of castration and testosterone administration on the urinary excretion of brush border proximal tubular enzymes (in that case only NAG and y-GT). However, the experiment was conducted in 'two kidney-one clip Goldblatt hyperten sion'.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the surgical and chemical castrations in these males reduced blood pressure levels down to the similar levels as observed in females (Reckelhoff, Zhang et al 1999). Similar results were reported in other castrated animal models (Malyusz and Ehrens 1983; Malyusz, Ehrens et al 1985; Woods, Morgan et al 2010). In addition, Ely et al found that the Tfm rat, lacking functional AR, and castrated rats have lower blood pressure than intact control rats (Ely, Salisbury et al 1991), suggesting that androgen/AR signaling might be involved in hypertension.…”
Section: Androgen/ar Roles In Hypertensionsupporting
confidence: 91%
“…The finding that the success rate of inducing renal hypertension in females was increased dramatically by prior ovariectomy, points to an influence of endogenous ovarian hormones on the development of hypertension in this model. Indeed, gonadal hormones have been reported to influence the onset and severity of hypertension in other hypertensive models [1,2,[20][21][22][23]. Although plasma hormonal levels were not measured in the present study, on completion of the study, the absence of ovarian tissue was confirmed and vaginal smears taken from the ovariectomized rats were similar to those obtained at stages of the oestrous cycle when levels of both oestradiol and progesterone are low [24].…”
Section: Discussionmentioning
confidence: 51%